Las sutilezas del poder en imágenes y algoritmos (Monográfico) - Bordignon, Gabriel Barros (2025)
The article starts from Foucault’s reflection, ‘where there is power, there is resistance’, to investigate the validity of this axiom in contemporary times, in which modalities of power that are exercised through images and algorithms are widespread and even encouraged in societies. The text builds a picture of the modalities of power over the centuries, starting with the physical punishments of the monarchical era, passing through disciplinary techniques, biopolitical strategies of government, the society of spectacle and the role of images, the power of consumption under neoliberalism, the societies of control described by Deleuze, the instrumental power of large technology companies that transform human behavior into profitable digital data, culminating with the current power of artificial intelligences (AI) and their autonomous learning technologies, which begin to mediate various everyday relationships and have the potential to remove the human being from social actions in different fields: individual, family, market, government, among others. It is argued that the evolution of the modalities of power follows the path of efficiency, subtlety and entertainment, being more and more accepted and less and less combated. Finally, the article reflects on the possibilities of contemporary resistances and the construction of collectivities in an individualistic world, taken by images in all instances of existence and mediated by programming codes.